2023
DOI: 10.1242/jeb.244733
|View full text |Cite
|
Sign up to set email alerts
|

Increased reliance on coronary perfusion for cardiorespiratory performance in seawater-acclimated rainbow trout

Abstract: Salmonid ventricles are composed of spongy and compact myocardium, the latter being perfused via a coronary circulation. Rainbow trout (Oncorhynchus mykiss) acclimated to sea water have higher proportions of compact myocardium and display stroke volume-mediated elevations in resting cardiac output relative to freshwater-acclimated trout, likely to meet the higher metabolic needs of osmoregulatory functions. Here, we tested the hypothesis that cardiorespiratory performance of rainbow trout in sea water is more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
1
0
0
Order By: Relevance
“…Future experiments should focus on a potential impairment of electrical conduction in the ventricular myocardium; Electrocardiogram (ECG) recordings have shown that a similar type of bradycardia, as observed here, occurred in rainbow trout following an exhaustive chase protocol to elicit maximum cardiorespiratory performance 51 , which was attributed to second degree atrio-ventricular block 52 , 53 . The atrio-ventricular canal of fish conducts action potentials from the sinoatrial pacemaker region to the ventricle, and in salmonids contains compact myocardium perfused by the coronaries 54 .…”
Section: Discussionsupporting
confidence: 60%
“…Future experiments should focus on a potential impairment of electrical conduction in the ventricular myocardium; Electrocardiogram (ECG) recordings have shown that a similar type of bradycardia, as observed here, occurred in rainbow trout following an exhaustive chase protocol to elicit maximum cardiorespiratory performance 51 , which was attributed to second degree atrio-ventricular block 52 , 53 . The atrio-ventricular canal of fish conducts action potentials from the sinoatrial pacemaker region to the ventricle, and in salmonids contains compact myocardium perfused by the coronaries 54 .…”
Section: Discussionsupporting
confidence: 60%
“…For instance, acclimation to seawater in rainbow trout, Oncorhynchus mykiss , results in higher proportions of compact myocardium compared with that of conspecifics in freshwater. This suggests an increased dependency on the coronary circulation, which provides oxygen‐rich blood to the compact myocardium, likely meeting the higher metabolic needs of osmoregulatory functions (Brijs et al., 2017 ; Wallbom et al., 2023 ). The salmonid heart is a highly phenotypically plastic organ and remodels across multiple levels of organization in response to environmental stimuli (Brijs et al., 2017 ; Gamperl & Farrell, 2004 ; Wallbom et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%